the teaching and research : meeting points in teacher training with political criteria - Navarro Monsalve, Yolanda; Alba,; Alicia, (Rastros Rostros, 2023)
Thinking about the training of teachers for this new century is a commitment that we have assumed with great responsibility within the two degree programs that this group of teachers has led together with the coordinator. In this issue of the magazine we want to place for discussion and enrichment of the proposal, part of a document that was worked on by all teachers of the degrees in January and whose main objectives were to make an analysis of the research process in the degrees and present the proposal of the German seminar to be implemented in teaching.
Keywords: teaching; research